Memoria 1986-1987. - Ivelic, Milan; Galeria Arte Actual, Santiago de Chile (Santiago de Chile : Galeria Arte Actual, 1987)
Miranda, Hernan ; Toral, Mario ; Garcia, Jose ; Baeza, Maria Angelica ; Orb, Consuelo ; Gewölb, Nancy ; Quiroz, Julio ; De La O, Patricio ; Ossa, Patricia ; Peña, Osvaldo ; Mesa, Ricardo ; Tacla, Jorge ; Gonzalo-Ilabaca, Yuri ; Cerda, Francisca ; Cadiz, Ruperto ; Cruz, Valentina ; Gatica, Omar ; Nuñez, Guillermo ; Mezza, Gonzalo ; Maturana, Carlos Bororo ; etc.
Spaans
boek